Alternative assessment to enhance theological education - Oliver, Erna (HTS teologiese studies, 2015)
The knowledge driven, network society that is founded upon technology, demands from students to become independent, confident and motivated life-long, self-directed learners that can transfer their knowledge, skills and values. In order to deliver this type of graduates from a diverse and unequal student pool, effective education must be provided. Educators are encouraged to focus education on student-centeredness and to use technology effectively. Alternative assessment methods that are technology driven could enable both educators and students to become more effective in this environment. This article advocates the use of alternative assessment methods by using technology driven assessment tools for possible replacement of traditional, paper based and ‘one size fits all’ assessment methods within theology. The SECTIONS framework was used to evaluate ten alternative assessment tools that are in accord with the development within society.